1992
DOI: 10.1002/ccd.1810250409
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary stent implantation via the brachial approach: A technique to reduce vascular bleeding complications

Abstract: To reduce the incidence of vascular complications of intracoronary stent implantation, we used the brachial approach. We attempted implantation of the Palmaz-Schatz stent via the brachial artery approach at 10 lesions in 9 patients. Stent delivery was successful at 8 lesions. Balloon angioplasty was successfully performed in the 2 failed cases, 1 of whom required surgical repair of the brachial artery. Intravenous anticoagulation was uninterrupted from the time of stent placement until therapeutic prothrombin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The incidence of local complications is undoubtedly influenced by the size of equipment used in the procedure, the type of access, and the skill of the operator. At Columbia Medical Center in Phoenix, we have found that devices larger than 8 French ate more frequently associated with local complications and that femoral access is more often linked to these occurrences than brachial access [15].…”
Section: Complicationsmentioning
confidence: 97%
“…The incidence of local complications is undoubtedly influenced by the size of equipment used in the procedure, the type of access, and the skill of the operator. At Columbia Medical Center in Phoenix, we have found that devices larger than 8 French ate more frequently associated with local complications and that femoral access is more often linked to these occurrences than brachial access [15].…”
Section: Complicationsmentioning
confidence: 97%
“…One thing is to attend forums discussing the benefit of the radial procedure or work with operators that perform these procedures on a routine basis. With over 25 years of experience performing the radial procedure, and after having written one of the earlier papers showing the benefit of the arm approach versus groin approach for PCI , we conduct frequent radial training programs to encourage our colleagues to perform this safer approach to modern day PCI. At the St. Luke's Medical Center in Phoenix, we looked at our last 12 month log of patients undergoing coronary intervention.…”
mentioning
confidence: 99%